Clinicopathological profile of patients with hepatobiliary cancers at two main referral hospitals in Lima, Peru - Machicado, Claudia (2022)
Objective: The aim of the study was to describe the clinicopathological profile of patients diagnosed with liver, bile ducts or gallbladder cancer. Materials and methods: Between 2006 and 2017, 89 patients (57% female; mean age: 62 years-old) with these cancers were diagnosed at two national hospitals in Lima, Peru. Results: Most patients (64%) had advanced stages of disease. Anemia was more frequent in patients with bile duct and liver cancer and in advanced stages. Hypertension (HTN) was frequent among liver cancer patients (32%). The analysis by age showed that HTN was more frequent in patients over 50 years. Likewise, people under 50 years had more frequent history of previous infections (50%), Hepatitis B (HBV) being the most co on. Conclusions: This study describes the baseline clinicopathological characteristics of a malignancy poorly studied in Peru.